Analisis Yuridis Putusan Kasasi Dibawah Ancaman Minimal dalam UU Narkotika: Studi Kasus Putusan Mahkamah Agung Nomor 4634 K/Pid.Sus/2023 - Ahmad Dzulkifli Rahmatullah; Muhamad Hasan Sebyar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
At the cassation level, the defendant's Narcotics crime, named Andhyka Murty Cahya Primandaka, has been determined in Law Number 35 of 2009 concerning Narcotics. In this case the defendant has undergone several levels of justice and finally the cassation level. The judge has given criminal sanctions less than the minimum limit regulated in the Narcotics Law. So this creates legal confusion that can be disputed because the judge does not examine and try a criminal case properly. This research aims to analyze juridically the cassation decisions issued under the minimum threat in the Narcotics Law. A case study was conducted on Supreme Court Decision Number 4634 K/Pid.Sus/2023. The research method used is a normative legal research method with a case study approach, namely examining statutory regulations and judges' decisions with the aim of finding out the reasons why judges impose criminal sanctions less than the minimum limit. The results of the research show that in the cassation decision there are problems related to the application of minimum threats in narcotics cases and the need for a review of the application of minimum threats in narcotics cases to ensure justice and legal effectiveness.